‘Violento é o estado!’: violência política nas práticas anarquistas contemporâneas - Grote, Florian (2018)
The present dissertation investigates the use of political violence in contemporary anarchist practices. The most important reflections on the debate about violence were presented and discussed, among them those of Walter Benjamin, Georges Sorel, Carl Schmitt and Hannah Arendt, to then unfold and amplify the criticism of Luis Felipe Miguel about the tendency of Contemporary Political Theory to eliminate violence and conflict from debate and reflection. For this, the post-structuralist critique of Michel Foucault, Giorgio Agamben, Gilles Deleuze and Jaques Derrida was introduced into the debate, aiming to present an apprehension of violence that is capable of reaffirming its irreducibility in political practice without, however, glorifying it. Not only did post-structuralist criticism reveal the subtle and insidious forms of political violence, in addition to its more obviously institutional aspects, but it also made it possible to reinsert the use of political violence and anarchist practices in political debate. In this sense, the paper investigated the violent practices of classic and contemporary anarchism, such as Black Blocs, Temporary Autonomous Zones (TAZ), direct action, sabotage and propaganda by the deed, that have played, for centuries, an irreducible role of resistance against repression and state violence. Finally, based on Charles Tilly's classified counts approach, the work sought to compare the confrontational repertoires of the Brazilian demonstrations of june 2013 with the recent protests against the 2017 G20 summit in Hamburg, with the aim of contributing to a better understanding of the so-called Jornadas de Junho and the recent political events in Brazil.